More asymptotic formulas for the generalized Stirling numbers of the first kind - Vega, Mary Ann Ritzell P.,; Corcino, Cristina B., (Utilitas Mathematica, 2008)
In this paper asymptotic formulas for the generalized Stirling numbers of the first kind Sα,γn,m, α, γ ε R., are obtained valid for the two subranges of m: 1 ≤ m ≤ o(logn); n - o(√n) ≤ m ≤ n.